PRODUCTION AND OPERATIONAL ACTIVITIES: MODERN INTERPRETATIONS OF ESSENCE AND RELATIONSHIPS OF CONCEPTS - KOROTKOVA, KSENIIA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
In the conditions of constant transformations of business and its main activity, the research of production and operational activity that, sometimes, is missed at research of all activity of the organization remains actual question. The purpose is to present the results of the study to clarify the essence and distinguish between the concepts of "production activity" and "operational activity of the organization". The article defines the concept of "production" and "production activity", which defines the creation of tangible products, ie material values. It is determined that production is aimed at creating a physical product by any means of labor. In the conditions of constant transformation of post-industrial society, development of high technologies, science-intensive productions and informatization of all spheres of life, interweaving and interaction of economic and social activity the sphere of services increasingly begins to prevail over the sphere of production. To confirm or refute this fact, statistical information on the ratio of production to services as of 2012 and 2019 was examined, and it is determined that by the criterion of the number of economic entities by type of economic activity, the service sector significantly outweighs the production sector (86% and 14%, respectively). That is why there is a need to separate the names of these activities. The terms "production" and "production activity" continued to be interpreted traditionally - as the manufacture of tangible products, and for the non-productive sphere was created an analogue - "operations". The authors' approaches to the essence of "operational activity" are considered and it is determined that this concept is broader than "production activity", as it includes the non-productive sphere and the sphere of services. The terms "production and operating activities" are distinguished.
Keywords: production; operations; production activities; operating activities; relationships of concepts